2018
DOI: 10.21037/atm.2018.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Frailty in elderly ICU patients in Greece: a prospective, observational study

Abstract: The findings of the study highlighted the onset of frailty syndrome in ICU patients. The objective assessment of the frailty syndrome of the seriously ill patient as well as the prognostic markers provides a clearer picture of its out-of-hospital condition and contributes to the collection of information on the outcomes of the in-hospital treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The advantages of LS are its simplicity and objectivity, which are essential in clinical use. Additionally, consistent with the results of the aforementioned trials with other frailty assessment tools [2, 5, 2527, 38], LS was an independent risk factor of in-hospital mortality in our analysis. Of note, we also found that the association between frailty and mortality was influenced by the presence of treatment limitations, i.e., patients with treatment limitations had high aOR of death regardless of their frailty status.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The advantages of LS are its simplicity and objectivity, which are essential in clinical use. Additionally, consistent with the results of the aforementioned trials with other frailty assessment tools [2, 5, 2527, 38], LS was an independent risk factor of in-hospital mortality in our analysis. Of note, we also found that the association between frailty and mortality was influenced by the presence of treatment limitations, i.e., patients with treatment limitations had high aOR of death regardless of their frailty status.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, there has been a growing understanding that frailty may be a more robust predictor of vulnerability than chronological age alone [24]. Several studies have reported that frailty is associated with both poor short-term [2, 5, 2527] and long-term [3, 4, 2830] outcomes in patients in the ICU. Therefore, several statements support the use of frailty in the triage [3136], as an entrance to the ICU, while making decisions with respect to treatment limitations [37], as an exit from the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, CFS was used evaluating frailty in older patients admitted in an intensive care unit. In this study 25% of the patients were categorized as frail, based on information adapted by the patients’ family or caregiver [ 45 ]. In the second one, CFS was used to assess the frailty status of hospitalized elderly patients with atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of frailty in community samples ranges from 6 to 11.1% [8][9][10]. Inpatients have a higher prevalence of frailty, ranging from 25 to 65.62% [11,12].…”
Section: Introductionmentioning
confidence: 99%